Anthropological View of Architecture: an Alternative Approach to Study Human Environments - Yimsrual, Supakit (Nakhara : Journal of Environmental Design and Planning, 2012)
Architectural descriptions mostly focus on the material aspects of a building with relatively little said about the social life of the people who inhabit architecture. In recent decades, many architects and anthropologists have begun to connect architectural works with the development of social and cultural anthropology. The term “architectural anthropology” has been suggested to describe the interrelation between humans and their built environment. Based on historical documents, this paper outlines the development of architectural anthropology and aims to illustrate how this approach can help us to understand the relation between people, their ideas of the world and the creation of a sustainable built environment.